The Contemporary Qur'anic Exegesis: Tracking Trends in The Interpretation of The Qur’an in Indonesia 2000-2010 - Zuhdi, M. Nurdin; Syamsuddin, Sahiron (JURNAL JAWI, 2018)
This study discusses the characteristics of the Qur'an interpretations in Indonesia which appeared in the last ten years (2000-2010). The focus of the study is to reveal and analyze the diversity and uniqueness of the Qur'an interpretations in Indonesia within 2000-2010 in terms of interpretation methods/ approach, interpretation style, and typology of thought interpretation. In spite of tracking the new trends that occur, this study also analyzes the contribution of Indonesian interpretation in the development of contemporary Qur'an tafseer thinking. This study employed a historical-sociological-critical approach and a contemporary Qur’an hermeneutic approach. The analysis conducted to 26 interpretations shows the diversity and uniqueness as follows: first, analysis of 26 interpretations has derived a new trend in the interpretation that the author called as Nusantara Tafseer Paradigm. Nusantara Tafseer Paradigm is an interpretation of verses of the Qur'an that has a nuance of Indonesian typical interpretation. Nusantara Tafseer Paradigm produces a product of interpretation which is relevant with the spirit of Indonesia in terms of culture (culture), customs, habits, language, climate, social, political, economic, and geographical of Indonesia. Second, the 26 analyzed interpretations produce 5 tafseer styles, namely: linguistic style, social-community style, fiqih style, theological style, and the scientific style. Third, the 26 analyzed interpretations produces four typologies of interpretive thinking: traditionalistic objectivist typology, objective revivalist typology, subjectivist typology and modernist objectivist typology. Fourth, the emergence of new trends in terms of paradigm, style and typology of thought interpretation in Indonesia has indicated a shift of interpretation paradigm that has not occurred in the previous periods. These new trends have a great contribution to the development of contemporary interpretation thought especially in Indonesia.